PERMODELAN MATEMATIKA EKSTRAKSI OLEORESIN TEMULAWAK (Curcuma Xanthorrizha Roxb) DENGAN KARBONDIOKSIDA SUPERKRITIS DAN CO-SOLVENT ETANOL MENGGUNAKAN SHRINKING CORE MODEL - Farah Fahma Dept. TIN (Department of Agroindustrial Technology, Bogor Agricultural University, 2006)
AbstractThis experiment studied the extraction of oleoresin from Curcuma Xanthorrizha Roxb using supercritical carbon dioxide. Effects of various operation condition such as pressure, temperature, extractions time, and addition of ethanol-co-solvent into bulk carbon dioxide have been studied. Solubility of carbon dioxide could be increased by addition of co-solvent ethanol. Temperature and pressure affect solubility of oleoresin in carbon dioxide so that it may affect to oleoresin, and curcuminoid yield. Extraction temperature and pressure were performed at 45-65 oC and 10-18 MPa, respectively. Simulation study that could describe the process of oleoresin extraction from Curcuma Xanthorhiza Roxb by supercritical carbon dioxide have been done using Shrinking Core Model. Fitting the calculated curve and experimental data done by trial the difference value of a and Bi, where a = (V/L) (R2/De) and Bi = (kf R/De). Effective inter particle diffusion value (De) and external mass transfer coefficient (kf) could be determined after trial value of a and Bi. At 14 Mpa, 50oC, with co-solvent, the resulted value of De is 6.572 x 10-11 and the value of kf is 1.2159 x 10-5 with error value 2.46 %. Keywords : modeling, supercritical carbon dioxide, Curcuma Xanthorrixa Roxb.